Regulation of Treasury Shares in Kuwaiti Law: A Comparative Study - Yousef Muhammad Altamimi (International Review of Law, 2024)
Treasury shares have a significant role in companies and capital markets’ regulations. As a result, it gained the attention of legislators and legal scholars. This paper examines the regulatory rules regarding treasury shares in Kuwaiti law, its philosophy, and practicality. The paper adopts a comparative, analytical approach addressing the historical evolution of treasury shares and comparing related regulations and legal provisions in many jurisdictions. With comparative law at hand, this paper aims to thoroughly examine the concept of treasure shares and their legal nature, their characteristics, buy-back procedures, treasury shares’ relation with the company’s capital structure, and ultimately, the uses of treasury shares. By analyzing Law No. 7 of 2010 Regarding the Establishment of the Capital Markets Authority and Regulating Securities Activities and Law No. 1 of 2016 Regarding Companies Law and by incorporating comparative law such as Swiss, German, Swedish, Danish and other laws, this study demonstrates different matters related to treasury shares that are not yet regulated in Kuwait. The research assesses the legal provisions governing treasury shares, addressing matters such as shareholder rights, voting power, and market manipulation concerns. It argues for regulatory reform to further enhance the provisions governing treasury shares. As a result of the analysis given, recommendations are provided to enhance the regulatory framework in Kuwait.